Students’ Perspectives on the Implementation of the Pancasila Student Profile Strengthening Project in Elementary Schools: A Kirkpatrick Model Evaluation Study - Mariani, Ni Nyoman; Witraguna, Kadek Yudista; Wirayani, Ni Made; Sukarini, Ni Made (Jurnal Pedagogi dan Pembelajaran, 2024)
The Pancasila Student Profile Strengthening Project (P5) in Elementary Schools has been implemented since 2022, but its implementation has never been evaluated. This study aims to evaluate the implementation of P5 with the Kirkpatrick evaluation model. This study is a type of evaluative research with a quantitative descriptive approach. The sample involved in this study was 36 elementary school students. Sample selection was carried out using the multi-stage sampling technique. Meanwhile, the data collection technique was carried out using a questionnaire and the data analysis technique used was descriptive statistics. The results of the study showed that the Implementation of the Pancasila Student Profile Strengthening Project (P5) reaction level and learning level were in the fairly good category, the behavior level and outcome level were in the good category. Participants' reactions to P5 were pleasant, students' knowledge, attitudes and skills also developed. Students were challenged to explore their knowledge, be creative, independent and responsible, and always try to innovate. Students' knowledge increased, students became more creative, independent, responsible and able to create new products. It can be concluded that the evaluation of the implementation of P5 with the Kirkpatrick evaluation model was carried out well. The latest information in this study can have implications for improving and enhancing the implementation of P5 in the future, so that it can create superior students.